2018
DOI: 10.1029/2018ja026037
|View full text |Cite
|
Sign up to set email alerts
|

Equatorial Evolution of the Fast Magnetosonic Mode in the Source Region: Observation‐Simulation Comparison of the Preferential Propagation Direction

Abstract: Recent analysis of an event observed by the Van Allen Probes in the source region outside the plasmapause has shown that fast magnetosonic waves (also referred to as equatorial noise) propagate preferentially in the azimuthal direction, implying that wave amplification should occur during azimuthal propagation. To demonstrate this, we carry out 2-D particle-in-cell simulations of the fast magnetosonic mode at the dipole magnetic equator with the simulation box size, the magnetic field inhomogeneity, and the pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(46 citation statements)
references
References 48 publications
7
39
0
Order By: Relevance
“…In fact, Němec et al () analyzed the electric field polarization ellipsoids of magnetosonic wave events acquired during multiple Cluster perigee passes. Their analysis indicated that azimuthal propagation is statistically dominant where the total plasma number density is low ( n030 cm 3 ), as occurs outside the plasmapause (plasma trough) and that the waves analyzed tended to possess a small radial component in their wave normal directions away from the Earth (consistent with the Min, Boardsen, et al ()'s simulation result). Considering that conditions outside the plasmapause are favored for wave excitation (e.g., Ma, Li, Chen, Thorne, & Angelopoulos, ; Yuan et al, ), this statistical result indicates that azimuthal propagation is indeed optimal for large wave amplification.…”
Section: Introductionmentioning
confidence: 54%
See 3 more Smart Citations
“…In fact, Němec et al () analyzed the electric field polarization ellipsoids of magnetosonic wave events acquired during multiple Cluster perigee passes. Their analysis indicated that azimuthal propagation is statistically dominant where the total plasma number density is low ( n030 cm 3 ), as occurs outside the plasmapause (plasma trough) and that the waves analyzed tended to possess a small radial component in their wave normal directions away from the Earth (consistent with the Min, Boardsen, et al ()'s simulation result). Considering that conditions outside the plasmapause are favored for wave excitation (e.g., Ma, Li, Chen, Thorne, & Angelopoulos, ; Yuan et al, ), this statistical result indicates that azimuthal propagation is indeed optimal for large wave amplification.…”
Section: Introductionmentioning
confidence: 54%
“…Under these conditions, the wave will remain in resonance for a longer time as it propagates azimuthally, allowing larger wave amplification. This has recently been confirmed by 2‐D PIC simulations of magnetosonic waves propagating perpendicular to the dipole magnetic field in the equatorial plane (i.e., waves with 90° wave normal angle; Min, Boardsen, et al, ). Using the plasma parameters from an event studied by Min, Liu, et al (), the simulations showed that magnetosonic wave amplification is dominant when the waves propagate azimuthally within the source region.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…Both satellite observations (Boardsen et al, 1992; Meredith et al, 2008; Perraut et al, 1982) and the linear theory (Chen et al, 2010; Gary et al, 2010; Sun, Gao, Chen, et al, 2016) have linked the generation of magnetosonic waves with ring distribution protons at energies of about 10 keV. Particle‐in‐cell (PIC) simulations in a uniform magnetic field (Liu et al, 2011; Sun, Gao, Lu, et al, 2016; Sun et al, 2017) and a dipole field (Chen et al, 2018; Min et al, 2018) have also demonstrated that the waves can be generated by ring distribution protons. In addition, one event study near or in the source suggests that the wave gain of the magnetosonic mode is primarily in the azimuthal direction (Boardsen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%